Eksistensi Peradilan Islam dalam Penyelesaian Perkara - Nurlaila Harun (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
The judiciary is one of the main pillars of the law enforcement system in Indonesia. In carrying out its primary function as an institution that upholds the law and justice, the courts are required to provide effective, efficient, and transparent services to the public. One crucial aspect of this service is case registration—the initial stage that determines how a case will be processed in court. The Religious Courts are one of the branches of the judiciary in Indonesia that play a vital role in upholding the law and justice for Muslims, particularly in the areas of Islamic family and civil law. In the Indonesian judicial system, case registration is the initial step that determines whether a case can be processed in court. Case registration serves as a formal request from the party seeking justice to resolve a dispute through legal mechanisms.